Validation of the ICP-MS method for determination of trace elements provided by ICH Q3D guideline in fosamprenavir calcium - Radić, Irena, kemičarka; Runje, Mislav; Cvetnić, Matija; Halužan, Maja; Jeličić, Mario-Livio; Miloloža, Martina; Kučić Grgić, Dajana; Prevarić, Viktorija; Ukić, Šime; Bolanča, Tomislav (2021)
Fosamprenavir calcium is an active pharmaceutical ingredient (API) in which trace elements must be monitored by ICH Q3D Guideline. It delivers appropriate method to ensure the quality of the product and its safe use. Elemental impurities in API are separated in three classes based on their toxicity and probability of their occurrence in the product. ICP-MS has proven to be a suitable technique with the appropriate sample preparation method. Due to the presence of oxidising agents in the sample preparation, determination of osmium is problematic. In the presence of oxidising nitric acid, a highly volatile and toxic osmium tetraoxide is formed. Due to its high volatility, the recovery of osmium has reached the value of 287 %, which exceeds recovery limit (70–150 %). However, osmium can be stabilised by complexation with thiourea in the hydrochloric acid solution (recovery = 87 %). In that way, the loss of osmium is reduced and good results are achieved in terms of usability, accuracy, and precision. A method with addition of thiourea has been successfully validated through main validation parameters: linearity, quantitation limit, selectivity, accuracy, precision (which included repeatability and intralaboratory reproducibility), and robustness. Each of these validation parameters met the acceptance criteria, and therefore it was concluded that the method is suitable for the determination of trace elements in fosamprenavir calcium by ICP-MS.
Fosamprenavir kalcij je aktivna farmaceutska tvar (API) u kojoj se elementi u tragovima moraju nadzirati prema ICH Q3D smjernicama. ICH Q3D smjernice donose odgovarajuću metodu za osiguravanje kvalitete proizvoda i njegove sigurne uporabe. Elementarne nečistoće u API-ju razdvajaju se u tri razreda na temelju njihove toksičnosti i vjerojatnosti da se pojave u proizvodu. ICP-MS se pokazala kao prikladna tehnika ako se primijeni odgovarajuća metoda pripreme uzoraka. Zbog prisutnosti oksidirajućih sredstava u pripremi uzoraka problem se javlja kod određivanja osmija. Osmij u prisutnosti oksidirajuće dušične kiseline daje visoko hlapljiv i toksičan osmij tetraoksid. Zbog visoke hlapljivosti, iskorištenje osmija iznosi 287 %, što premašuje zadanu granicu iskorištenja (70 – 150 %). Međutim, osmij se može stabilizirati kompleksiranjem s tioureom u otopini klorovodične kiseline (povrat od 87 %). Na taj se način smanjuje njegov gubitak, a postižu se dobri rezultati u pogledu točnosti, preciznosti i robusnosti metode.
Bibliografija: 18 jed.
Abstract ; Sažetak.
Keywords: ICP-MS -- Mikrovalna digestija -- Farmaceutska tvar -- Fosamprenavir kalcij -- Tragovi metala